Hydrogen sulfide improves endothelial dysfunction in hypertension by activating peroxisome proliferator-activated receptor delta/endothelial nitric oxide synthase signaling. Issue 3 (March 2018) - Xiao, Lin; Dong, Jing-Hui; Teng, Xu; Jin, Sheng; Xue, Hong-Mei; Liu, Shang-Yu; Guo, Qi; Shen, Wei; Ni, Xiao-Chen; Wu, Yu-Ming
Abstract : Objective: We aimed to elucidate the ameliorative effect of hydrogen sulfide (H2 S) on endothelium-dependent relaxation disturbances via peroxisome proliferator-activated receptor delta/endothelial nitric oxide synthase (PPARδ/eNOS) pathway activation in hypertensive patients and rats. Methods: Renal arteries were collected from normotensive and hypertensive patients who underwent nephron-sparing surgery. Renal arteries from 37 patients were cultured with or without sodium H2 S (NaHS) 50 μmol/l. The rats were randomly divided into four groups: Sham; Sham + NaHS, two kidneys; one clipped (2K1C); and 2K1C + NaHS. Mean arterial pressure was measured by tail-cuff plethysmography. A microvessel recording technique was used to observe the effect of NaHS on endothelium-dependent relaxation. Plasma H2 S concentrations were detected using the monobromobimane method. Real-time PCR and western blotting were used to assess mRNA and protein levels of AT1, cystathionine γ-lyase, PPARδ, and phosphor-eNOS. Laser confocal scanning microscopy measured intracellular NO production in human umbilical vein endothelial cells. Results: NaHS improved endothelial function in hypertensive humans and rats. The 20-week administration of NaHS to 2K1C rats lowered the mean arterial pressure. In human umbilical vein endothelial cells, NaHS improved the AngII-induced production of NO. NaHS upregulated PPARδ expression, increased protein kinase B (Akt) or adenosine monophosphate kinase-activated protein kinase (AMPK) phosphorylation, and enhanced eNOS phosphorylation. A PPARδ agonist could mimic the ameliorative effect of NaHS that was suppressed by PPARδ, AMPK, or Akt inhibition. Conclusion: H2 S plays a protective function in renal arterial endothelium in hypertension by activating the PPARδ/PI3K/Akt/eNOS or PPARδ/AMPK/eNOS pathway. H2 S may serve as an effective strategy against hypertension.